Consumers' macroeconomic expectations - Lena Dräger; Michael Lamla (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2023)
After the financial crisis of 2008, central banks around the world have increased their communication efforts to reach consumers, with the aim of both guiding and anchoring their inflation expectations. For the expectations channel of monetary policy to work as intended, central banks need a thorough understanding of the formation process of expectations by the general public and of the relationship between expectations and economic choices. This warrants reliable and detailed data on consumers' expectations of macroeconomic variables such as inflation or interest rates. We thus survey the available survey data and issues regarding the measurement of macroeconomic expectations. Furthermore, we discuss the research frontier on important aspects of the expectations channel: We evaluate the evidence on whether expectations are formed consistently with standard macroeconomic relationships, discuss the insights with respect to the anchoring of inflation expectations, explore the role of narratives and preferences and lastly, we survey the research on causal effects of central bank communication on expectations and economic choices.
Keywords: E52; E30; D84; C83; 330; Consumers' macroeconomic expectations; central bank communication; survey data